Avaliação da aprendizagem no ensino remoto em escolas do campo no Amapá no periodo pandêmico - Rodrigues, Emanuel Tocantins (2024)
This Research Report aims to analyze the learning assessment process in rural schools in Amapá, during the 2020-2021 pandemic period. The study was carried out using a qualitative approach, in which documentary research and a bibliographic review were carried out based on the reading and analysis of Decrees, Ordinances and Technical Notes, published by the State Education Council and the State Department of Education of the State of Amapá, regarding teaching and assessment of learning during the pandemic period. Scientific articles, magazines, periodicals, master's dissertations were also analyzed, among which are those developed by Luckesi (2011) about the mistakes in the evaluation process, Hoffmann (2019) about dialogical mediation in learning evaluation, Santos (2014) with the practice of formative assessment in online education and Caldart (2002) with the role of rural schools in ensuring quality of teaching for students, specifically during the period of remote teaching. The studies demonstrate the structural deficiency of school units located in the countryside in relation to the use of digital tools in the process of evaluating students' learning during the pandemic period caused by Covid-19. It also highlights the pedagogical instruments used by teachers to assess learning during remote teaching.